Public policy and rural-urban migration. - Cm, Becker; Ar, Morrison (Journal of Political Economy, 1997)
A wide range of public policies which affect rural-urban migration is surveyed and evaluated. Direct controls upon migration are the least significant except under strong authoritarian regimes. However policies which reduce the natural rate of population growth can have major impacts upon rural-urban migration and urban population growth. Efforts to promote secondary cities and market towns in hopes of redirecting rural-urban migration have been constrained by the large infrastructure investments they demand. It has been extremely expensive to relocate capital cities and tax incentives to affect the location of private firms have been problematic. Policies which decentralize government hold greater promise but they are not likely to be welcomed by central government officials. Policies which target the rural or urban sector can have a major impact upon rural-urban migration. The most important determinants of rural-urban migration however are macroeconomic policies. It remains to be seen whether structural adjustment programs implemented in Latin America will slow the pace of rural-urban migration.